세계농업 전망모형 Aglink 2006 운용·개발연구 : 브라질 대두 생산이 국내 및 세계 대두시장에 미치는 파급영향 - 김배성 (한국농촌경제연구원, 2006)
The Aglink model is a dynamic recursive simulation model and a demand- supply partial equilibrium model of the world agricultural sector. The model was developed by the OECD Secretariat in cooperation with member countries in 1993 and has been used to draw up the OECD world agricultural outlook and simulations for various policy analyses. As this study will be carried out continuously year by year, the final aim is to build a sufficient application capacity to analyze the world agricultural market and to indicate future directions for Korea’s agricultural policies. The major research contents of our report for this year are as follows: In the 1st chapter, the research background, aims of this study, the review of preceding researches, and a brief explanation of imported variables in the Aglink model are introduced. In the 2nd chapter, we reviewed the current status and the outlook of the world soybeans and oilseed markets. And in the 3rd chapter, we reviewed the current status of soybeans supply and demand and their trade in Brazil. In the 4th chapter, the researchers evaluated Korea's current issues of the soybean market. And we made possible scenarios in the 2nd and 3rd chapter’s conclusions and assessed the results of each scenario. In the 5th chapter, we introduced a Brazilian module of Aglink 2006 to elevate the degree of understanding of the Brazil oilseeds module. Researchers: Bae-Sung Kim, Young-Su Cho, and Young-Ho Lee e-mail Address: bbskim@krei.re.kr